Combination of Tapping with Eccentric Exercise and Passive Stretching on Handgrip Ability of Elbow Tennis Patients - Maya Triyanita; Hendrik Hendrik (Health Notions, 2022)
Tennis elbow is a complaint of pain in the forearm which usually radiates to the dorsum of the hand due to inflammation or non-specific degeneration of the extensor carpi radialis brevis (ECRB) muscle in the lateral epicondyle of the humerus as a result of repetitive hand activities. This study aims to determine the differences in the effects of tapping and eccentric exercise with tapping and passive stretching on increasing grip strength in tennis elbow patients. This research was an experimental study with a randomized control group pretest-posttest design. This research was conducted on the campus of the Department of Physiotherapy, Poltekkes Kemenkes Makassar, Indonesia. The population was 45 patients who have tennis elbow, aged between 30-45 years, and do not have other neuromusculoskeletal disorders. The sample was obtained using the Lemesow formula so that a sample size of 40 subjects was taken using a simple random sampling technique, then divided into two groups randomly, namely the group given tapping and eccentric exercise and the group being given taping and passive stretching. Both groups were given the intervention three times a week for four weeks. The results of the Wilcoxon test analysis showed that tapping and eccentric exercise interventions significantly increased gripping ability with p-value = 0.000 (<0.05) while tapping and passive stretching interventions showed a significant increase in gripping ability with p = 0.003 (<0.05). The results of the Mann-Whitney test analysis showed that there was a significant difference between groups in the ability to grip with a p-value = 0.006 (<0.05). Thus it can be concluded that the intervention with a combination of tapping affects the gripping ability of tennis elbow patients. Keywords: tennis elbow; eccentric exercise; passive stretching; tapping; grip strength